Предмет: Математика, автор: lbondikov

Помогите решить 10.2 пожалуйста

Приложения:

Ответы

Автор ответа: Аноним
0

4(\frac{2}{3} )^{2x-2} + 2*9^x-11*2^x = 0\\\\4(\frac{2}{3} )^{2x}:(\frac{2}{3})^2  + 2*9^x - 11*2^x = 0\\\\9(\frac{2}{3} )^{2x} + 2*3^{2x} - 11*2^x = 0 | :(\frac{2}{3} )^{2x} \\\\9+2*(\frac{9}{2} )^{2x}-11*(\frac{9}{2} )^{x} = 0

Пусть (\frac{9}{2} )^{x} = t :

9+2t^2-11t = 0\\\\2t^2-11t+9 = 0\\\\D = (-11)^2-4*2*9 = 121-72 = 49=7^2\\\\t_1 = \frac{11+7}{2*2} =\frac{18}{4} =\frac{9}{2} \\\\t_2 = \frac{11-7}{2*2} =\frac{4}{4} =1

Обратная замена :

(\frac{9}{2} )^x = \frac{9}{2} \\x = 1

------------

(\frac{9}{2} )^x = 1\\x = 0

Ответ : 1, 0

Похожие вопросы
Предмет: Русский язык, автор: Pele20050329